bankruptcy BANKRUPTCY PREDICTION FOR COMPANIES USING THE ALTMAN Z-SCORE MODEL (A CASE STUDY IN LEASING COMPANIES IN INDONESIAN STOCK EXCHANGE PERIODE 2019-2021) - Rena Mustari Mokoginta; Heince R N Wokas (Universitas Sam Ratulangi, 2022)
This study aimed to determine which lieasing companies on the IDX are predicted to go bankrupt between 2019 and 2021 using the Altman Z-Score model. This research utilised descriptive research. Samples were collected using the nonprobability sampling technique. Based on the predetermined criteria, 14 financing companies were acquired as the study samples. The method employed was the Altman Z-Score model. The study results from 2019-2021 showed ten financing companies in healthy condition, one company is predicted to be in a grey area, and two companies are predicted for bankrupt. One company was predicted in a grey area in 2019 and entered a healthy condition from 2020-2021.